METHODS OF CONDUCTING PHYSICAL EDUCATION ACTIVITIES IN THE DEVELOPMENT OF PRESCHOOL CHILDREN - Abdukarimov Nurmakan Amirkanovich (Journal of Higher Education and Academic Advancement, 2024)
In this article, information on the methods of organizing physical education classes by educators in preschool educational institutions is applied